Kepatuhan Pasien Diabetes Melitus Dalam Mengendalikan Kadar Gula Darah Di Wilayah Desa Sampalowo Kecamatan Petasia Barat Kabupaten Morowali Utara - Lilian, Estelle; Kantohe, Imelda; Alfira Yunita, Anggri (CV. Multi Kreasi Media, 2024)
The results of the researcher's initial interviews with 2 people suffering from diabetes mellitus in the Sampalowo village area obtained information that these patients were less compliant in undergoing treatment. This can be seen from their explanation that the patient does not take medication regularly and does not control blood sugar regularly. The increase in patient blood sugar levels is also caused by not always adopting a healthy diet, not exercising, not following a diet program, stress, smoking and consuming alcoholic drinks. The aim of this research is to determine patient compliance in controlling blood sugar levels in the Sampalowo Village Area, Petasia Barat District, North Morowali Regency. This type of research is descriptive. The variable in this study is patient compliance in controlling blood sugar levels to prevent diabetes mellitus. Data types are primary and secondary. Data collection uses a questionnaire. Data analysis uses univariate analysis. The population in this study were all patients suffering from diabetes mellitus in the Sampalowo village area, namely 32 people. The sample consisted of 32 people. The results showed that of the 32 respondents in this study, 59.4% were more compliant in controlling blood sugar levels compared to 40.6% who were less compliant. The conclusion in this study is that patients in the Sampalowo Village area, Petasia Barat District, North Morowali Regency are more likely to have good compliance in controlling blood sugar levels. The suggestion in this research is that it is hoped that patients will always regularly control blood sugar levels and always adopt a healthy lifestyle.